2018
DOI: 10.1108/ejtd-05-2018-0044
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship programs in the manufacturing industry

Abstract: Purpose This paper aims to present a literature review of studies of mentorship programs in the manufacturing industry so as to lay a theoretical basis for learning at work. Design/methodology/approach A literature review with focus on mentorship programs in the manufacturing industry was used. A search for relevant peer-reviewed articles, in four databases, rendered 315 hits, but only one article dealt with mentorship programs in an industry similar to the manufacturing industry. Thus, it is concluded that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In this article, we identified common principles that reflect the value of mentorship in This study is consistent with the literature on mentorship in workplace learning programs. The only review of the literature of mentorship programs in blue collar occupations, which drew mostly on business-oriented mentorship programs as a proxy for programs in the manufacturing sector, found that previous studies explored definitions of mentorship, the characteristics of good mentors, and mentorship program structures 8 with many findings that mirror ours. However, previous mentorship literature across occupations often situates mentorship programmatic goals within a traditional organizational development and human resources paradigm, which aims at improved worker satisfaction, higher worker productivity and better retention of high performing employees.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In this article, we identified common principles that reflect the value of mentorship in This study is consistent with the literature on mentorship in workplace learning programs. The only review of the literature of mentorship programs in blue collar occupations, which drew mostly on business-oriented mentorship programs as a proxy for programs in the manufacturing sector, found that previous studies explored definitions of mentorship, the characteristics of good mentors, and mentorship program structures 8 with many findings that mirror ours. However, previous mentorship literature across occupations often situates mentorship programmatic goals within a traditional organizational development and human resources paradigm, which aims at improved worker satisfaction, higher worker productivity and better retention of high performing employees.…”
Section: Discussionsupporting
confidence: 62%
“…Mentorship has been identified as one comprehensive approach to supplement traditional classroom learning, especially for adult learners, to develop and reinforce leadership skills 7 and to apply knowledge to problem-oriented work situations. 8 The mentoring experience, especially between peer mentors, facilitates transformational learning whereby pre-existing knowledge and ideas are challenged, and new learning is applied to solve a problem. 9 Mentorship is a form of leadership training that is applied to real life situations.…”
Section: Introductionmentioning
confidence: 99%
“…ICT is the key enabler to enhance knowledge flow between companies and their suppliers through improving access to knowledge and eliminating temporal and spatial obstacles among individuals [35], [39]. The use of ICT can further improve individual perception regarding the ease of sharing knowledge [36], broaden the understanding of supplier organization culture to determine supplier responses toward knowledge sharing in the supplier development program [2], and assist in selecting the appropriate knowledge sharing mechanism [5], [37].…”
Section: Information and Communication Technologymentioning
confidence: 99%
“…Mentorship is a relationship in which a more experienced or more knowledgeable person helps to guide a less experienced or less knowledgeable person [6]. Mentorship includes mentoring activity [5] that requires bidirectional communication between mentor and mentee, where the mentee should be proactive in receiving and implementing the knowledge [21]. In knowledge sharing activity of the supplier development program, knowledge adheres to mentors as the firm members performing the mentoring [2].…”
Section: E Mentorshipmentioning
confidence: 99%
“…The concept of spillover is commonly associated with knowledge and economic transfer from one region to another, or across industries. Knowledge flows can also be observed at more localized levels, within an industry or within a company, for instance when skills are transferred from experts to a novice (Bjursell and Florin Sädbom, 2018 ). In the context of innovation, collaborative patterns in patent activities have been faster in information diffusion compared to weak ties (Wang et al, 2017 ).…”
Section: Previous Literaturementioning
confidence: 99%